The Role of Managers’ Compensation in the Relationship Between Integrated Reporting and Firm Value - Wardhani , Kartika Sukma; Utami, Evy Rahman (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Currently, financial reports alone are considered not to reflect the company's condition, so other information is needed to meet investors' needs. Then, integrated reporting appears, which contains company information, including both financial and non-financial information. Integrated reporting uses integrated information to increase firm value, which attracts investor interest. This research aims to analyse the influence of integrated reporting on firm value, the influence of manager compensation on firm value, and whether manager compensation can moderate the influence of integrated reporting on firm value. The population in this research includes all companies listed on the Indonesia Stock Exchange (BEI) for the 2022 period. The purposive sampling method selects 486 companies that meet the criteria for this research. This reseach relies on descriptive statistics and hypothesis testing. The research results show that integrated reporting does not affect firm value because integrated reporting is considered to require large costs and takes a long time to prepare. The test results in this study also show that manager compensation has no effect on firm value, and manager compensation does not strengthen the relationship between integrated reporting and firm value because the manager's offer makes the manager only fulfil it, not aiming to increase firm value to attract investors.